Relapsing Polychondritis Can Be Characterized by Three Different Clinical Phenotypes: Analysis of a Recent Series of 142 Patients. Issue 12 (December 2016) - Dion, Jérémie; Costedoat‐Chalumeau, Nathalie; Sène, Damien; Cohen‐Bittan, Judith; Leroux, Gaëlle; Dion, Charlotte; Francès, Camille; Piette, Jean‐Charles
Abstract : Objective: Relapsing polychondritis (RP) is a rare condition characterized by recurrent inflammation of cartilaginous tissue and systemic manifestations. Data on this disease remain scarce. This study was undertaken to describe patient characteristics and disease evolution, identify prognostic factors, and define different clinical phenotypes of RP. Methods: We performed a retrospective study of 142 patients with RP who were seen between 2000 and 2012 in a single center. Results: Of the 142 patients, 86 (61%) were women. The mean ± SD age at first symptoms was 43.5 ± 15 years. Patients had the following chondritis types: auricular (89%; n = 127), nasal (63%; n = 89), laryngeal (43%; n = 61), tracheobronchial (22%; n = 32), and/orcostochondritis (40%; n = 57). The main other manifestations were articular (69%; n = 98), ophthalmologic (56%; n = 80), audiovestibular (34%; n = 48), cardiac (27%; n = 38), and cutaneous (28%; n = 40). At a mean ± SD followup of 13 ± 9 years, the 5‐ and 10‐year survival rates were 95 ± 2% and 91 ± 3%, respectively. Factors associated with death on multivariable analysis were male sex ( P  = 0.01), cardiac abnormalities ( P  = 0.03), and concomitant myelodysplastic syndrome (MDS) ( P  = 0.004) or another hematologic malignancy ( P  = 0.01). Cluster analysis revealed that separating patients into 3 groups was clinically relevant, thereby separating patients with associated MDS, those with tracheobronchial involvement, and those without the 2 features in terms of clinical characteristics, therapeutic management, and prognosis. Conclusion: This large series of patients with definite RP revealed an improvement in survival as compared with previous studies. Factors associated with death were male sex, cardiac involvement, and concomitant hematologic malignancy. We identified 3 distinct phenotypes.